Time Series Analysis of Sea Surface Temperature With Aqua MODIS from 2011 to 2016. Case Studi: North Coast of Gresik and Madura - Hendrata Wibisana; Siti Zainab (IPTEK The Journal for Technology and Science, 2017)
Sea surface temperature (SST) is a measurement parameter for the condition of coastal and marine water quality, where the value of SST is a measure of fertility of ecosystems in the waters concerning the lives of flora and fauna. To measure the SST can be done by several methods, simple by using a alcohol thermometer dipped into the sea and water bodies to obtain the existing value of the SPL. To measure a wider area in order to obtain a global picture of course is not effective to measure in situ, we need a technology and methods that can replace the monitoring of the global SST, for the purposes of the use of remote sensing technologies by using algorithms that have been widely used. As the material in this study used satellite imagery Aqua Modis 250 meters during January from 2011 to 2016 that can instantly detect the SST value at some predetermined coordinates and as a case study area have Gresik coast towards the northern part of the island of Madura. The results obtained from this study is that the range value of standard deviation and variation of the average value of SST per year, which the SST is in the range of 27oC to 32oC, and from linear regression obtained an average value of R squared of 0.748 for a period of 6 years the process of aquisition of satellite imagery. The coastal area around the north Pangkah Gresik has the highest temperature is 31oC while the waters to the north of Madura has an average temperature of 28oC.